2013
DOI: 10.1074/jbc.m112.415240
|View full text |Cite
|
Sign up to set email alerts
|

HectD1 E3 Ligase Modifies Adenomatous Polyposis Coli (APC) with Polyubiquitin to Promote the APC-Axin Interaction

Abstract: Background: APC is modified with Lys-63-linked polyubiquitin when bound to Axin in an assembled ␤-catenin destruction complex. Results: HectD1 E3 ligase modifies APC with Lys-63-linked ubiquitin chains to facilitate the APC-Axin interaction. Conclusion: HectD1 is a candidate E3 ligase for APC. Significance: The identification of HectD1 could lead to a better understanding of APC function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 56 publications
3
78
0
Order By: Relevance
“…2G). It has been previously reported that hTNKS1 coIPs with hAPC1 (27), suggesting that either TNKS binds APC1 via a non-consensus motif we were unable to identify, or that TNKS is in a complex with APC1 but lacks direct binding.…”
Section: Tnks Binds Drosophila Apc2 At a Conserved C-terminalmentioning
confidence: 49%
“…2G). It has been previously reported that hTNKS1 coIPs with hAPC1 (27), suggesting that either TNKS binds APC1 via a non-consensus motif we were unable to identify, or that TNKS is in a complex with APC1 but lacks direct binding.…”
Section: Tnks Binds Drosophila Apc2 At a Conserved C-terminalmentioning
confidence: 49%
“…Hectd1 is a HECT domain E3 ubiquitin ligase that plays an important role in development of the neural tube (Sarkar and Zohn, 2012; Zohn et al, 2007) and regulation of Wnt signaling (Tran et al, 2013). Ubiquitin conjugated substrates are widely distributed in the endometrium and decidua in rodents and primates (Bebington et al, 2000), and studies of mouse mutants demonstrate that ubiquitin dependent modification plays an indispensable role in placental development.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing findings regarding nonproteolytic ubiquitination through atypical ubiquitin linkages also have noted this pathway. For example, K63-linked polyubiquitination of Dvl is considered to promote Wnt signaling transduction (17), while HectD1-mediated antigen-presenting cell (APC) ubiquitination through K63 ubiquitin linkage inhibits Wnt signaling by facilitating axin-APC interaction (18). The E3 ligase EDD, targeting ␤-catenin via K11-or K29-linked polyubiquitination, was reported to stabilize ␤-catenin instead of triggering its degradation (19).…”
mentioning
confidence: 99%